THE ROLE OF TIME AND EXPERIENCE TO THE GYMNASTICS FOR ALL PRACTICE: BUILDING A SENSE OF COLLECTIVITY - Fernanda Raffi Menegaldo; Marco Bortoleto (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
This essay aims to discuss the role of two sociological categories, time and experience, in a particular context of a non-competitive gymnastics practice (Gymnastics for All - GfA). Understanding GfA as a group activity, the collective participation becomes a key element to allow the participants to share experiences in an extended time. This collective experience in GfA seems to be directly related to development and maintenance of social relations and promotion of the sense of belonging, which reinforce GfA as a body practice that defies the performance and the individualization logic that is overly experienced in the contemporary society.